Book of abstracts of the 27th Colloquium of African Geology: 17th Conference of the Geological Society of Africa - Silva, Eduardo Ferreira da (2019)
On behalf of the Local Organizing Committee of “27th Colloquium of African Geology/17th Conference of the Geological Society of Africa – CAG27”, we would like to welcome you to this important meeting regarding “Africa: The key player for a better and sustainable world” that we feel privileged to host. This Conference, sponsored by the Universidade de Aveiro and the GeoBioTec Research Centre, under the auspices of the Geological Society of Africa (GSAf), is an opportunity to continue the scientific exchanges between researchers from all over the world in the field of Geosciences, and to demonstrate the high scientific research standards that are being carried out over the world. The participants in the conference will have the opportunity to share their expertise in a range of scientific fields, such as geology, geological resources, environmental risks, environment and human health, sustainable development, education, and tourism in Africa. (...)